Conceptual Model Study on Environmental Entrepreneurship in the Framework of Corporate Social Responsibility in Hotels - IŞILDAR, PINAR (International Journal of Contemporary Economics and Administrative Sciences, 2022)
This study aims to create a holistic conceptual model that integrates environmental entrepreneurship in hotels and with the corporate social responsibility model adopted as a sustainable business model under a single structure. In this context, by integrating environmental initiatives carried out in hotels into Caroll's corporate social responsibility model, a sustainable holistic structure was tried to be created in hotels. To research the integration of environmental entrepreneurship in CSR sustainable business models in-depth, the explorative methodology was used and a qualitative research method was adopted. Findings suggest that environmental initiatives in hotel businesses are gathered under the economic, legal, ethical, and philanthropic dimensions determined in the corporate social responsibility model. Among the environmental initiatives classified according to the results obtained, the most striking environmental initiatives were the environmental initiatives that provided economic benefit with 49.64%. Later, they were classified as environmental initiatives that provided a positive image with 28.35%, provided legal obligations with 15.44%, and were completely carried out with voluntary donations at 6.61%. As a result of the literature review and research findings, a holistic conceptual model has been proposed. Keywords: Environmental Entrepreneurship, Corporate Social Responsibility, Sustainable Business Model, Sustainablity